Simple and validated method to quantify lacosamide in human breast milk and plasma using UPLC/MS/MS and its application to estimate drug transfer into breast milk - Ayako Furugen; Ayako Nishimura; Takeshi Umazume; Hina Ishikawa; Katsuya Narumi; Masaki Kobayashi (Journal of Pharmaceutical Health Care and Sciences, 2023)
Abstract Background Epilepsy is a common neurological disorder. Lacosamide is a third-generation antiepileptic drug used to treat partial-onset seizures. Limited information is currently available on the transfer of lacosamide to breast milk. To facilitate studies on the safety of lacosamide use during breastfeeding, we aimed to develop a method to quantify lacosamide in human breast milk and plasma using ultra-performance liquid chromatography/tandem mass spectrometry. Methods Fifty microliters of breast milk or plasma was used, and samples were prepared by protein precipitation using methanol containing lacosamide-d3 as an internal standard (IS). Chromatography was performed using an ACQUITY HSS T3 column with an isocratic flow of 10 mM ammonium acetate solution/methanol (70:30, v/v). Lacosamide and IS were detected by multiple reaction monitoring in positive ion electrospray mode. The run time was 3.5 min. Results Calibration curves were linear and in the range of 0.5 to 100 ng/mL both in breast milk and plasma. The validation assessment indicated that precision, accuracy, matrix effects, selectivity, dilution integrity, and stability were acceptable. The developed method was successfully applied to quantify lacosamide in breast milk and plasma obtained from a volunteer who had been orally administered lacosamide twice a day (100 mg × 2). Relative infant dose of lacosamide was estimated to be 14.6% in breast milk at five time points. Conclusions We developed a simple and robust method to quantify of lacosamide in human breast milk and plasma. This method could be useful for in future studies investigating the safety of lacosamide use during breastfeeding.